The effect of work environment on organizational performance in Wisma Perkeso Kuching, Sarawak / Muhammad ‘Izzat Bahauddin Zulkipli and Presela Dobrah Bennet Empam - Zulkipli, Muhammad ‘Izzat Bahauddin; Bennet Empam, Presela Dobra (2018)
The main purpose of this research is to know whether work environment can affect the performance of the organization. Nowadays, work environment is not being considered as an important element in order to improve the performance of the organization. Thus, we would like to evaluate the perception of the employees towards the environment at their workplace. In the work environment, we divide it into two which is the physical work environment and the non-physical work environment which. Both the physical work environment and the non-physical work environment consist of several elements which were being used in previous study. Hence, we also try to find out which of those two types of work environment give more effect on the performance of the organization. We will conducted this research at the Wisma PERKESO Kuching, Sarawak as the organization are located in the city which quite suitable for our purpose of study. The findings of the study are hoped to provide idea to the employer and the upper level management on how to increase the performance of the organization in term of the work environment.